Pengaruh Status Sosial Ekonomi dan Intensitas Bimbingan Belajar terhadap Prestasi Akademik Siswa pada Mata Pelajaran Ekonomi - Nur Atia; Mustafa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of socioeconomic status and the intensity of tutoring on students' academic achievement in Economics at State Senior High School 16, South Konawe. This type of research is quantitative research with an ex post facto approach. The study population consisted of all 80 students of class XI IPS of State Senior High School 16, and the entire population was sampled (saturated sampling). The independent variables in this study are socioeconomic status (X₁) and the intensity of tutoring (X₂), while the dependent variable is Economics learning achievement (Y). Data collection techniques used questionnaires to obtain data on socioeconomic status and tutoring, as well as documentation to obtain learning achievement data. Data analysis was carried out using multiple linear regression tests using the SPSS program. The results of the study are expected to show that: (1) socioeconomic status has a positive and significant influence on student learning achievement; (2) the intensity of tutoring has a positive and significant influence on student learning achievement; and (3) socioeconomic status and the intensity of tutoring simultaneously have a significant influence on student academic achievement in Economics. These findings are expected to contribute to improving the quality of education through attention to students' socio-economic conditions and optimizing tutoring activities, both in and outside of school. Keywords: Socioeconomic Status, Tutoring, Academic Achievement